Extruded high-temperature thermoplastic tufting yarns for enhanced mechanical properties of composites. (April 2020) - McGarrigle, Cormac; Fernández, Daniel; Middendorf, Peter; Dooher, Thomas; Kelly, John; McIlhagger, Alistair; Harkin-Jones, Eileen; Archer, Edward
Through-thickness stitching, in the form of tufting, has been shown to be a potentially successful method of improving resistance to delamination. Tufting is a single-sided stitching technique that involves the insertion of a yarn through a fabric, in the z-direction. However, further research into the development of a tailored tufting yarn could yield a greater improvement in the mechanical properties of the overall composite. Unlike other published works which rely on commercially available materials, for this study four thermoplastic yarns were produced from polyetheretherketone, polysulfone, polyethersulfone and polyphenylsulfone. Their ability to be tufted into a composite was examined along with their influence on the overall mechanical properties of the composite.